Feminismos, interseccionalidades e questões de gênero: enunciações de docentes do curso de biologia. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
I understand science as a male undertaking that, by articulating power and knowledge, produced/produces discriminatory discourses, which are criticized by feminist epistemologies. The teaching discourse often propagates the regimes of truth produced by science. Based on these reflections, I ask: how are feminisms, intersectionalities and gender issues enunciated in the speeches of university professors in the field of biology? What reflections about the Teaching of Science and Biology can be made in view of these discourses? The general objective of the research is to analyze the discourse of teachers, in relation to feminisms, intersectionalities and gender issues in society and science, meaning them from feminist epistemologies, having as specific objectives to identify statements related to feminisms, intersectionality and gender issues in science and knowledge of biology; and rethinking possibilities for the Teaching of Science and Biology from the teachers' speeches. The research is qualitative and feminist, based on post-critical, Foucaultian references and on feminist theories and epistemologies of science. The participants were six professors working in the Licentiate Degree in Biological Sciences at a Public University in Paraná. The corpus of analysis was built through semi-structured interviews, carried out online. The discourses were analyzed from the Foucaultian perspective, using Foucault's tools – discourse, statement, power-knowledge relations – and feminist theorizations, to highlight the statements and silences of the discourses and give them meaning. I listed three discursive axes, which refer to feminisms, intersectionality and gender issues in Biology. As for feminisms, they enunciated a liberal feminism, silencing pluralities, fear of calling themselves a feminist, and an explanation that reinforces the stereotype of submissive woman and protective man. The intersectionalities were silenced and a meritocratic discourse expressed when thinking about access to science. They enunciated the gender disparities in science and the difficulties encountered by women in this area. When thinking about gender issues in Biology, they enunciated criticisms of the contents, descriptions and methodology of the area, and discourses articulated to feminist epistemologies. They also criticized propositions of racism in Biology and a stereotyped and sexist language. On the other hand, they enunciated exchange of subjectivisms inverting the roles between females and males, in addition to the discourse of a neutral and decontextualized science, and sexist discourses, which reinforce social stereotypes based on Biology. From the speeches, I rethink the Teaching of Science and Biology and propose that we be feminist teachers, attentive to the different forms of oppression and that they think about teaching in a situated way. I emphasize that new paths need to be taken in search of a critical and plural teaching.
Keywords: Ensino de Ciências e Biologia; Epistemologias feministas; Discursos docentes; Science and Biology Teaching; Feminist Epistemologies; Teaching speeches; CNPQ::CIENCIAS EXATAS E DA TERRA::MATEMATICA